1998
DOI: 10.1083/jcb.143.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Radixin and Moesin Alters Growth Cone Morphology, Motility, and Process Formation In Primary Cultured Neurons

Abstract: In this study we have examined the cellular functions of ERM proteins in developing neurons. The results obtained indicate that there is a high degree of spatial and temporal correlation between the expression and subcellular localization of radixin and moesin with the morphological development of neuritic growth cones. More importantly, we show that double suppression of radixin and moesin, but not of ezrin–radixin or ezrin–moesin, results in reduction of growth cone size, disappearance of radial striations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(185 citation statements)
references
References 54 publications
11
173
0
1
Order By: Relevance
“…An apoptotic property of these cells was observed both in vitro and in tumor tissues. Our results are consistent with previous finding in hippocampal pyramidal cells (Paglini et al, 1998). The observed effects of radixin silencing on the GBM cell transformation indicate a role for radixin in regulating tumor metastasis and progression.…”
Section: Discussionsupporting
confidence: 83%
“…An apoptotic property of these cells was observed both in vitro and in tumor tissues. Our results are consistent with previous finding in hippocampal pyramidal cells (Paglini et al, 1998). The observed effects of radixin silencing on the GBM cell transformation indicate a role for radixin in regulating tumor metastasis and progression.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, immunoelectron microscopy has revealed that microtubules penetrating into the growth cone peripheral domain contain MAP1B and interact with actin filament bundles (Bush et al, 1996;Gordon-Weeks and Fischer, 2000). Therefore, by favoring the existence of dynamic microtubules within growth cones, MAP1B may contribute to the promotion of lamellipodial spreading, an event required for neuronal polarization Dotti, 1997, 1999;Paglini et al, 1998b). In favor of this idea, we observed a significant reduction in the size of the lamellipodial veil and a decrease in the number of actin ribs in axonal growth cones of MAP1B-deficient neurons.…”
Section: Discussionmentioning
confidence: 99%
“…C ells were fixed before or after detergent extraction under microtubule-stabilizing conditions and processed for immunofluorescence as described previously (Paglini et al, 1998a). For some experiments a mild extraction protocol that preserves cytoskeletalmembrane interactions was also used (Nakata and Hirokawa, 1987;Brandt et al, 1995;Paglini et al, 1998b).…”
Section: Methodsmentioning
confidence: 99%
“…In cultured hippocampal pyramidal neurons, axon formation is preceded by the appearance in one of the multiple neurites of a large and highly dynamic growth cone containing a very labile actin network Dotti, 1997, 1999;Paglini et al, 1998a). Thus, the regulation of actin organization and activity within selected growth cones appears to be one of the major factors underlying the establishment of neuronal polarity.…”
Section: Abstract: Tiam1; Microtubules; Microfilaments; Axons; Growtmentioning
confidence: 99%
See 1 more Smart Citation